Giant Brain Abscess in a Neonate Managed with External Drainage - Sedain, G; Ali, N; Bhattachan, M; Sharma, MS; Shilpakar, SK (Journal of Nepal Paediatric Society, 2013)
Brain abscesses in neonates are extremely rare and usually occur in patients with certain risk factors. A 26 days child presented to the emergency with fever, irritability and not sucking well. CT revealed a large left frontal lobe abscess which was managed with burr hole and a drainage tube with concurrent intravenous antibiotics. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7317 J Nepal Paediatr Soc. 2013;33(1):55-56